Karađorđevići in vladarska ideologija pri Slovencih - Repe, Božo (Studia Historica Slovenica, 2023)
The article deals with the attitude of Slovenes towards royalty and compares the personality cult of the three most important rulers in contemporary history: the Austro-Hungarian Emperor Franz Joseph from the Habsburg family, the Yugoslav King Alexander from the Karađorđević family, and the leader of the Yugoslav communists and President of the Socialist Federal Republic of Yugoslavia Josip Broz Tito. The author shows how the cult of personality developed during their rule, what it looked like after the collapse of the countries they ruled, and what the attitude toward all three rulers is today.
Keywords: Aleksandar Karađorđević; Aleksander; Austro-Hungarian Monarchy; Avstro-Ogrska; Broz, Josip; Franc Joseph; Franz, Joseph; Habsburg (rodbina); Josip Broz-Tito; Karađorđević (rodbina); Kingdom of Serbs, Croats and Slovenes (Yugoslavia); Kraljevina Srbov Hrvatov in Slovencev (Jugoslavija); kult osebnosti; monarchy; monarhija; personality cult; Socialist Federal Yugoslavia; Socialistična federativna republika Jugoslavija (SFRJ); vladavina; Zgodovina